(untitled) (jornal of the libyan geographical society, 1997)
Soil is a complex and constantly changing substance. In addition to being a support for plants, it provides them with the water, air, and nutrients they need. It consists of solid particles, the largest of which is very coarse sand, with a diameter not exceeding 21 mm (and the smallest is clay, with a diameter less than 21 mm). All materials with diameters greater than 21 mm are classified as gravel and rocks and are not considered soil. Soil particles are grouped based on size without considering chemical composition, density, or color. The process by which soil particles are separated from each other in the laboratory is called "particle size analysis".